SEARCH FOR DECAYS OF THE W+/-BOSONS AND Z-BOSONS INTO QUARK ANTIQUARK PAIRS - Ansari, R; Bagnaia, P; Banner, M; Battiston, R; Bernlohr, K; Booth, C; Borer, K; Borghini, M; Carboni, G; Cavasinni, V; Cenci, P; Chollet, J; et al. (1987)
The invariant mass distribution of jet pairs observed in the UA2 central calorimeter is examined in the search for an excess of events in the region of the W± and Z bosons, which would reveal their decays into quark-antiquark pairs. We give a detailed account of the methods of analysis used to optimize the mass resolution achieving ≅±10%. A structure is observed at the level of ≅ 3 standard deviations in the mass region of W± and Z with shape and position consistent with expectation from their qq̄decays. It contains 632 ± 190 events, 1.4 standard deviations above the standard model prediction of 340 ± 80 events. © 1987.